Numerical Calculation of Pressure Loss and Forced Convective Heat Transfer In Rotating Channels of Arbitrary Rectangular Cross Section - Schilling, R. (Engineering Transactions, 1981)
The steady fully-developed laminar flow field and temperature field in rotating straight rectangular channels is investigated by a finite difference method. The solution of the Navier-Stokes equations and the energy equation yields the pressure loss, beat transfer and the efficiency factor as a function of the Reynolds number, Rotation number and aspect ratio. The numerical results agree well with available experimental data.